FINANCING INNOVATION IN ROMANIA - SORIN SERBAN (Challenges of the Knowledge Society)
This article based on an examination of empirical literature, analyses the financing of innovative enterprises in Romania and presents the characteristics of Romanian policies in this regard. It sets forth an estimation of the number of innovative enterprises in Romania based on figures from different sources. Assessing the role of financial restrictions on innovation reveals that a firm is facing obstacles to finance its innovative activities but also other difficulties to innovate which appears to be enhanced. This article also puts forward the role of different financing actors and instruments at different stages of the firm's life cycle and emphasizes the function of proximity capital in filling the gap between supply and demand of financing. Finally a framework for policy is recommended.